(untitled) (The Research of Medical Science Review, 2024)
Benign prostatic hyperplasia (BPH) is a common condition in older men, often managed surgically with Transurethral Resection of the Prostate (TURP) when symptoms are severe. Postoperative bleeding control remains a significant challenge, with Foley catheter traction frequently used for hemostasis. This study aims to compare the outcomes between patients undergoing Transurethral Resection of the Prostate (TURP) with Foley traction versus without Foley traction, This cross-sectional study was conducted at Department of Urology Jinnah Postgraduate Medical Centre, Karachi, included 60 posts TURP patients aged 50–65 years at the time of surgery for prostate enlargement with prostate volume <60 ml. Patients were randomized using sealed envelopes to either Group A (Foley Traction) and Group B (Non-Foley Traction). Bipolar TURP was conducted under a general anaesthetic with a 24Fr 3-way catheter and saline irrigation after surgery. Group A were received 2-hour Foley traction while Group B did not. Data were analysed with SPSS version 26.0, using t-test and Chi-square tests with P ≤ 0.05 was considered as statistical criteria significant, In this study, the sample size consisted of 60 patients in whom Transurethral Resection of the Prostate (TURP) was performed, which included 30 Foley traction-patients and 30 non-Foley traction group. Mean Age was 61.87 ± 3.98 in the Foley traction group and 62.77 ± 3.90 in the non-Foley group (p=0.380) Operative time was longer (65.20 ± 13.00 vs 74.63 ± 12.91 minutes; p=0.007), pain score (VAS 4.80 ± 2.00 vs 2.70 ± 0.87; p=0.0001), catheter time (61.83 ± 19.45 vs 48.67 ± 14.79 hours; p=0.005), and duration of hospital stay (4.93 ± 1.38 vs 4.10 ± 1.42 days; p=0.025) in patients with Foley traction than in without Foley insertion. There were no differences within postoperative complications like the retention of clots (6.7% vs. 3.3%; p=0500) while urinary retention was noted in (13.3% v/s 10.0%; p=0500), It is to be concluded that foley traction during TURP demonstrates potential benefits in enhancing hemostasis, reducing postoperative pain, and shortening hospital stay, collectively suggesting improved recovery outcomes. Rates of complications, including clot retention, urinary retention, and urge incontinence, were comparable between groups, indicating that Foley traction doe not increase the risk of adverse postoperative events. These findings suggest that Foley traction may promote effective hemostasis, enhance patient comfort, and support earlier discharge, reinforcing its utility as a valuable adjunct in TURP procedures without compromising patient safety.